Early Graft Failure after Coronary Artery Bypass Surgery: A Case of Anastomosis Detachment Due to Fibromuscular Dysplasia - Andrea Lorenzo Vecchi; Roberta Maragliano; Fausto Sessa; Cesare Beghi; Roberto De Ponti; Battistina Castiglioni (Hearts, 2021)
Fibromuscular dysplasia is a non-atherosclerotic, non-inflammatory arteriopathy, considered a rare cause of coronary artery disease. Although familial cases have been described, no specific gene association has been detected so far. When the coronary vessels are involved, the main clinical scenarios are stable angina, acute coronary syndromes, left ventricular dysfunction, and sudden death. Specific clinical and angiographic findings may suggest this as the underlying disease, but certain diagnosis histological. The involvement of the lower and upper limbs is unusual; however, it may have decisive clinical implications for the most appropriate revascularization method and the selection of the arterial graft to be used.